Web 2.0 as a pedagogical strategy in the process of English language teaching-learning - Contreras Salas, Olga Lucía (Rastros Rostros, 2012)
This article summarizes the results of the macro research project entitled “Interaction between ict and bilingual teaching as a functional learning alternative”, carried out at the Escuela Normal Superior de Bucaramanga from 2010 to 2012 by students of the Basic Education program with emphasis in Spanish and English, Universidad Cooperativa de Colombia, Bucaramanga. This proposal emphasized only Web 2.0, specifically developing the working platform of the English and Virtuality program at the Universidad Nacional Abierta y a Distancia, Florida; we used YouTube and blogs as educational tools. The main goal of the process was to get teachers to use new technologies in their teaching processes